2018
DOI: 10.1101/295048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect Size and Power in fMRI Group Analysis

Abstract: Multi-subject functional magnetic resonance imaging (fMRI) analysis is often concerned with determining whether there exists a significant population-wide 'activation' in a comparison between two or more conditions. Typically this is assessed by testing the average value of a contrast of parameter estimates (COPE) against zero in a general linear model (GLM) analysis. In this work we investigate several aspects of this type of analysis. First, we study the e↵ects of sample size on the sensitivity and reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 30 publications
(46 reference statements)
0
53
0
Order By: Relevance
“…These results also highlight the problems inherent in studying associations between variables derived from low‐sensitivity methods, such as fMRI and MRS, in terms of the sample sizes required. For fMRI research, recent work has helped demonstrate the limits of making inferences from small samples, suggesting that larger groups (>100) than have normally been used are necessary for robust and replicable analyses . Equivalent studies for MRS are not yet available, but the meta‐analysis reported here helps illustrate the problem in this context.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results also highlight the problems inherent in studying associations between variables derived from low‐sensitivity methods, such as fMRI and MRS, in terms of the sample sizes required. For fMRI research, recent work has helped demonstrate the limits of making inferences from small samples, suggesting that larger groups (>100) than have normally been used are necessary for robust and replicable analyses . Equivalent studies for MRS are not yet available, but the meta‐analysis reported here helps illustrate the problem in this context.…”
Section: Discussionmentioning
confidence: 95%
“…For fMRI research, recent work has helped demonstrate the limits of making inferences from small samples, suggesting that larger groups (>100) than have normally been used are necessary for robust and replicable analyses. 30,31 Equivalent studies for MRS are not yet available, but the meta-analysis reported here helps illustrate the problem in this context. Adding the current results to five previous studies produced overall evidence for a negative association between GABA estimates and BOLD amplitudes (total sample size = 100).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that eect size estimates resulting from the thresholding of mass-univariate statistical parametric maps exhibit biases (e.g., Vul et al, 2009;Poldrack et al, 2017). To correct our eect size estimate for this bias, we capitalized on recent results by Geuter et al (2018), which are depicted in the lower panel of Figure 4A. Specically, using task-related fMRI data from the Human Connectome Figure 4A, this eect size bias is most severe for small data subsets and decreases with increasing data subset size.…”
Section: Exemplary Applicationmentioning
confidence: 99%
“…In the recent debate on the reproducibility of research ndings in the life sciences, the statistical practices of fMRI research have once again taken centre stage in the community discourse (e.g., Eklund et al, 2016;Mumford et al, 2016;Poldrack et al, 2017;Eklund et al, 2019;Flandin and Friston, 2019). Here, a particular emphasis has been on statistical power and its relation to typical sample sizes in fMRI group studies (Button et al, 2013;Guo et al, 2014;Szucs and Ioannidis, 2016;Cremers et al, 2017;Geuter et al, 2018;Turner et al, 2018). In task-related fMRI, statistical power is broadly dened as the probability of detecting cortical activation, if this activation is indeed present.…”
Section: Introductionmentioning
confidence: 99%
“…The sample sizes of the fMRI experiments were determined to be comparable to or larger than other neuroimaging studies of motivational biases 105 and curiosity-based effects 5,6 . Also, such a sample size should be sufficient to reliably detect medium effect sizes in task-based fMRI analysis 106 .…”
Section: Statement On Statistics and Reproducibilitymentioning
confidence: 99%